Enhancing the Learning of Body Systems through ClassPoint - Assisted Interactive Instruction - U. Alvez, Michelle; Anne C. Taleon, Josephine (Journal of Neonatal Surgery, 2025)
This study, which assessed the effectiveness of ClassPoint-assisted interactive learning in improving students' performance and engagement level, has significant practical implications. The study utilized the ClassPoint application to teach learning body systems to Grade 10 students at Toledo City Science High School during the 2024-2025 school year. A quasi-experimental research design was employed, involving 40 respondents. An adapted questionnaire from Abellera (2020), Calma (2020), and Tamayo (2020) was utilized for the pretest and posttest to evaluate students' knowledge of the specified learning competencies in Science 10. Additionally, a survey questionnaire measuring students' engagement levels was adapted from Bong and Chatterjee (2021). The findings indicate that the control and experimental groups performed poorly on the pretest, showing a significant difference in two of the three assessed learning competencies. With the experimental group scoring better, this study found a significant difference in posttest performance between the two respondent groups. These results underline how well ClassPoint-assisted interactive learning increases student knowledge and involvement in science education. The findings showed that students had a reasonable opinion of Classpoint, which helped them to be very engaged. More interactive teaching tools should be included in the educational process to promote even more interesting learning opportunities.